Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/jxb/erac085
|View full text |Cite
|
Sign up to set email alerts
|

Stress, senescence, and specialized metabolites in bryophytes

Abstract: Life on land exposes plants to varied abiotic and biotic environmental stresses. These environmental drivers contributed to a large expansion of metabolic capabilities during land plant evolution and species diversification. In this review we summarise knowledge on how the specialised metabolite pathways of bryophytes may contribute to stress tolerance capabilities. Bryophytes are the non-tracheophyte land plant group (comprised of the hornworts, liverworts and mosses) that rapidly diversified following the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 140 publications
(244 reference statements)
0
17
0
Order By: Relevance
“…Populus leaves turn yellow in autumn, a consequence according to chlorophyll degradation during senescence in response to environmental change 29 , 30 . The present study showed that concentrations of phenolic acids in leaves were more highly elevated at the beginning of the spring period and decomposed at the end of the active season until leaves maturity 31 . 32 found that willow trees’ degraded structure and growth rate turn down on senescence leaves in relation to low leaf water potential.…”
Section: Discussionmentioning
confidence: 47%
“…Populus leaves turn yellow in autumn, a consequence according to chlorophyll degradation during senescence in response to environmental change 29 , 30 . The present study showed that concentrations of phenolic acids in leaves were more highly elevated at the beginning of the spring period and decomposed at the end of the active season until leaves maturity 31 . 32 found that willow trees’ degraded structure and growth rate turn down on senescence leaves in relation to low leaf water potential.…”
Section: Discussionmentioning
confidence: 47%
“…Each color represents the pathway present in each bryophyte group. PAL, phenylalanine ammonia-lyase; C4H, cinnamate 4-hydroxylase; 4CL, 4-coumarate:CoA ligase; CHS, chalcone synthase; CHI, chalcone isomerase; CHIL, chalcone isomerase-like; F3H, flavanone 3-hydroxylase; DFR, dihydroflavonol 4-reductase; FNR, flavanone reductase; IFS, isoflavone synthase; HID, 2-hydroxyisoflavanone dehydratase; ANS, anthocyanidin synthase; PPO, polyphenol oxidase (AUS/AS, aureusidin/aurone synthase); FNS, flavone synthase; FLS, flavonol synthase (Adapted from Davies et al 2020; Demehin et al 2022; Kulshrestha et al 2022; Wang et al 2005; Yonekura-Sakakibara et al 2019). Online pdf in color.…”
Section: Resultsmentioning
confidence: 99%
“…These three lineages form a unique part of the vegetation. They are small-sized, structurally simple diversified plants able to adapt to most ecosystems on Earth [ 1 , 2 ]. Bryophytes and tracheophytes (non-vascular and vascular plants, respectively) derive from an ancestral land plant and diverged during the Cambrian, some 500 million years ago [ 3 ].…”
Section: Introductionmentioning
confidence: 99%